Early rehabilitation interventions for global developmental delay in children: a narrative review - Liu, Shixian; Zhu, Meijun; Yi, Caiying; Zeng, Dongmei (Frontiers in Pediatrics, 2025)
The proactive action taken towards delays in global development is presumed to be key in enhancing the development of a child who possesses developmental difficulties. This article provides a review on the effectiveness and various impacts of different forms of early initiatives taken on multiple developmental stages. This review focuses on the results and changes brought forward through various intervention strategies such as physical therapy, occupational and speech therapy, as well as psychological interventions using research evidence available. Early action has a meaningful impact on the development of motor functions, cognitive abilities, social skills, language skills, and skills related to socialisation. Physical therapy is most effective in enhancing motor development when these interventions are provided within a particular scheme of evidence-based practices. Approaches in occupational therapy are greatly beneficial in enhancing independence and daily living skills for children. Demonstration-based speech therapy have increasingly favourable results in both understanding and using language, especially when surrounding intervention programmes work within detail. Along with other critical issues, the review focuses on elements affecting the effectiveness of the intervention, including factors related to the intervention, individual aspects, and the environment. The research outcomes underline the needs for family-centred and holistic approaches to early intervention and its ramifications on family and social systems. Attention is paid to service intensity, timing of the intervention, and the use of several treatment methods as instrumental in achieving the best possible developmental results. Service accessibility and other socio-cultural factors constitute other important environmental aspects that influence the success of an intervention. The findings support the necessity of adopting appropriate stakeholders in the intervention planning while observing proper practices and evaluations. From the review, we can determine that early detection and intervention are necessary to ensure optimal developmental outcomes. Evidence suggests that a thorough, integrated approach to intervention, if employed with adequate degrees of intensity and family inclusion, can greatly improve development in many areas. These findings are essential to clinical practice, service models, and policies regarding early intervention services.